Balancing pressures for SENCos as managers, leaders and advocates in the emerging context of the Covid‐19 pandemic. (1st March 2021) - Clarke, Amy L.; Done, Elizabeth J.
Abstract : This article considers the role of the SENCo during Covid‐19 pandemic conditions of school lockdown with partial reopening for children classified as 'vulnerable'. It is argued that the existing pressures and tensions already experienced by SENCos – for example, related to time, workload, status, and their prescribed managerial and strategic role – have been highlighted by pandemic conditions. Pressures resulting specifically from the pandemic are reflected by considering how SENCos will adjust to enact their role during this time. It is concluded that an advocacy role for pupils with special educational needs and disability, who are at risk of becoming increasingly marginalised within school and wider communities during this pandemic, should now be considered a central element of the SENCo's remit.